Financing Asia's infrastructure: modes of development and integration of Asian financial markets - Biswa Bhattacharyay (Asian Development Bank Institute (ADBI), 2010)
Asia faces very large infrastructure funding demands, estimated at around US750 billion per year for energy, transport, telecommunications, water, and sanitation during 2010-2020 (ADB/ADBI 2009). Asia has large savings, significant international reserves, and rapid accumulations of funds that could be utilized for meeting these infrastructure investment needs, but Asian markets have failed to use available resources to channel funding into highly needed infrastructure projects. This paper explores issues and challenges in financing infrastructure for seamless Asian infrastructure connectivity and for other high priority development financing needs, and seeks methods and instruments to help direct Asian and international resources to cost-effectively and efficiently support infrastructure and other development needs. The paper discusses three important topics: First, what are the lessons for Asia from the European Union's experience of developing and integrating financial markets and using development banking institutions to support infrastructure investment? Second, how can Asian public and private resources, such as pension funds, social security funds, sovereign wealth funds, and private portfolio funds contribute to infrastructure development across Asia? Third, can Islamic financial markets provide funds for Asian infrastructure development? Finally, the paper makes recommendations regarding financing options and how Asian financial markets and infrastructure companies could be further developed and integrated to mobilize Asian and other regions' savings for financing priority infrastructure projects in the region.
Keywords: G10; G20; G42; G48; 330; Infrastrukturinvestition; Kapitalmarktliberalisierung; Marktintegration; Entwicklungsfinanzierung; Asien